Makna Leksikal Udang di Balik Batu dalam Ungkapan - Ayuni, Zelpi; Feranti, Nadila; Safitri, Meili; Hermandra, Hermandra (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
Language often changes along with the times and its speakers. Language as a means of expression and communication in human life such as in the fields of culture, science and technology. The development of the influence of the western world that makes changes to the language in Indonesia such as vocabulary and terminology. The research method used in this research is a type of qualitative research that is descriptive and carried out using analysis. The process and meaning are more cenerung in this study with theory as a foundation to focus on research in accordance with the field, the results and research of this study require in-depth analysis to obtain data. Lexical semantics refers to lexical meaning, or the meaning that exists in a lexeme even though there is no explicit context. For example, the lexeme buya (crocodile) has a lexical "a type of slithering animal" meaning. Therefore, the lexical meaning is equivalent to the ordinary meaning of language/expression is a combination of words whose meaning has been fused and does not need to be interpreted with the meaning of the elements that make it up. Based on the results of the study, there is a lexical meaning in the expression "There are shrimp behind the stone", the lexical meaning in the expression "There are shrimp behind the stone" is to strengthen an idea in a hidden way. By using the terms "shrimp" and "stone", this expression illustrates the activeness of the language.